If we are all journalists, can journalistic privilege survive? - Gleason, Timothy W. (Javnost (Ljubljana), 2015)
The breaking down of the technological and economic barriers to reporting news and information creates the potential for any citizen to reach large audiences; however, it does not make all information-sharing activity "journalism", nor does it make everyone a "journalist". The challenge is to draw meaningful distinctions in this new environment that fully recognise and honour the democratisation of the information ecosystem, while at the same time preserving the ethical and legal standards and practices that distinguish journalism and journalists. Special protections or rights for journalists, if defined in narrow terms, are inconsistent with today's media ecosystem, where many independent voices have potential access to large audiences and the opportunity to contribute to civic debate. At the same time, a privilege is by definition not available to all. The existence of a journalistic privilege requires that a defined category of journalist exists. Dispute over the definition of journalist in the Executive Session provision of the Oregon Public Meetings law and the efforts to define journalists in state and federal confidential source protection statutes, court rulings and proposed legislation give us rich examples of the challenges faced in attempting to craft journalistic privileges for today's media environment.
Keywords: Digital media; Elektronski mediji; Journalism; New technologies; Nove tehnologije; Novinarstvo